2019
DOI: 10.1016/j.heliyon.2019.e01508
|View full text |Cite|
|
Sign up to set email alerts
|

Protein supplement consumption is linked to time spent exercising and high-protein content foods: A multicentric observational study

Abstract: The main aim of this study is to analyze if protein supplement consumption and food patterns vary across three geographical regions and secondly to identify possible factors that increase the likelihood of ingesting protein supplements. A total of 916 responses from gym users of 3 countries (Italy, Turkey and UK) were entered for analysis. Questions were related to supplement consumption (protein and other supplements), food intake and training habits. A descriptive analysis, analysis of variance (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
1
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
0
12
1
7
Order By: Relevance
“…Dietary supplements (DS) are food products containing dietary ingredients intended to supplement the diet with more nutritional value, and they include vitamins, minerals, amino acids, herbs or botanicals, and other substances [ 1 ]. There is a lot of evidence on the widespread use of DS in various countries [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. In Saudi Arabia, many studies have shown that the consumption of DS is becoming increasingly popular, particularly among fitness center attendees.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary supplements (DS) are food products containing dietary ingredients intended to supplement the diet with more nutritional value, and they include vitamins, minerals, amino acids, herbs or botanicals, and other substances [ 1 ]. There is a lot of evidence on the widespread use of DS in various countries [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. In Saudi Arabia, many studies have shown that the consumption of DS is becoming increasingly popular, particularly among fitness center attendees.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have also shown that the prevalence of consuming supplements is generally higher in males compared with females [ 3 , 4 , 24 , 25 ]. Among US Military Personnel, 42% reported using proteins or amino acids, and factors independently associated with DS use included female gender (OR female/male: 1.91; 95% CI: 1.73, 2.11) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, the application and processing of proteins in food, biological, pharmaceutical and chemistry industries have increased due to their use as food supplement (i.e. whey protein) 1 , 2 , hormones, vaccines, antibiotics, antibodies and biopharmaceutical enzymes 3 , among others. Obtaining high quality proteins for delivery to the final consumers is a major concern of the industries and, for this reason, the processing of proteins is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated that the early intake of protein following training, in amounts of 0.25–0.30 g/kg bodyweight (17.5–21.0 g for a 70 kg person), can help to rebuild and strengthen muscle fibres affected during intense training [ 6 ]. Protein powder supplements are recognised by athletes and gym users as an efficient means of meeting this requirement [ 7 ]. The recommended daily intake of protein for adequate nutrition has been reported to be between 0.8 and 1.2 g/kg bodyweight (56–84 g per day for a 70 kg person) [ 8 ], with higher intakes of up to 3.1 g/kg bodyweight suggested for more active individuals looking to increase performance and enhance muscle mass [ 6 , 7 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Protein powder supplements are recognised by athletes and gym users as an efficient means of meeting this requirement [ 7 ]. The recommended daily intake of protein for adequate nutrition has been reported to be between 0.8 and 1.2 g/kg bodyweight (56–84 g per day for a 70 kg person) [ 8 ], with higher intakes of up to 3.1 g/kg bodyweight suggested for more active individuals looking to increase performance and enhance muscle mass [ 6 , 7 , 9 , 10 ]. However, currently there is no evidence to suggest that daily consumption in excess of 3.0 g protein/kg bodyweight provides any additional benefit to consumers [ 7 ].…”
Section: Introductionmentioning
confidence: 99%